(3ajQhS chQhfG GdLOjO (B:s (3GdJOGYjGJ GdGbJUGOjI hGdGSJQGJjLjI Ydi GdUjf hGdYGde (B/s - (3TQja, eMehO (B((3GdGbJUGO(B)s ([(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3eQcR JQjfOR ddHMhK hGdGSJTGQGJ,s, 2020)
(3jJfGhd gPG GdcJGH BKGQ XghQ (B"(3ajQhS chQhfG GdLOjO(B" (3aj GdUjf fgGjI TgQ OjSeHQ GdeGVj, hGfJTGQg Gdeghd OGNd GdUjf hNGQLgG MGdI ef GdPYQ hGdgdY GeJOJ Edi GdYGde cdg, hCYGOJ ef LOjO GdfbGTGJ Mhd NWQ GdChHFI GdajQhSjI, hGdJOGYjGJ GdJj jecf Cf JJQJH YdjgG Ydi UYO eNJdaI(B: (3GdEfSGfjI hGdGbJUGOjI hGdGSJQGJjLjI hGdCefjI hMJi GdKbGajI(B. (3ceG CYGO Edi GdSGMI GdYGdejI ef LOjO GdLOd Mhd eSGFd eQJHWI HGdajQhSGJ GdhHGFjI; eKd XGgQI GdMQhH GdHjhdhLjI GdJj bO JTgO JWhQGJ NWjQI eSJbHdG HaVd GdJWhQ GdePgd aj Ydhe GdLjfhe, hGdgfOSI GdhQGKjI, hJWHjbGJ GdPcGA GdGUWfGYj GdeQJHWI HGdeLGd GdHjhdhLj hGdUMj(B.s
Keywords: (3ajQhS chQhfG GdeSJLOs -- (3LhGfH GbJUGOjIs; (3ajQhS chQhfG GdeSJLOs -- (3LhGfH SjGSjIs; (3ajQhS chQhfG GdeSJLOs -- (3LhGfH GbJUGOjIs -- (3GdUjfs; (3ajQhS chQhfG GdeSJLOs -- (3LhGfH SjGSjIs -- (3GdUjfs